Functional Analysis of the Carbohydrate-Binding Domains of Erwinia chrysanthemi Cel5 (Endoglucanase Z) and an Escherichia coli Putative Chitinase - Simpson, Helen D. (American Society for Microbiology, 1999)
The Cel5 cellulase (formerly known as endoglucanase Z) from Erwinia chrysanthemi is a multidomain enzyme consisting of a catalytic domain, a linker region, and a cellulose binding domain (CBD). A three-dimensional structure of the CBD(Cel5) has previously been obtained by nuclear magnetic resonance. In order to define the role of individual residues in cellulose binding, site-directed mutagenesis was performed. The role of three aromatic residues (Trp18, Trp43, and Tyr44) in cellulose binding was demonstrated. The exposed potential hydrogen bond donors, residues Gln22 and Glu27, appeared not to play a role in cellulose binding, whereas residue Asp17 was found to be important for the stability of Cel5. A deletion mutant lacking the residues Asp17 to Pro23 bound only weakly to cellulose. The sequence of CBD(Cel5) exhibits homology to a series of five repeating domains of a putative large protein, referred to as Yheb, from Escherichia coli. One of the repeating domains (Yheb1), consisting of 67 amino acids, was cloned from the E. coli chromosome and purified by metal chelating chromatography. While CBD(Cel5) bound to both cellulose and chitin, Yheb1 bound well to chitin, but only very poorly to cellulose. The Yheb protein contains a region that exhibits sequence homology with the catalytic domain of a chitinase, which is consistent with the hypothesis that the Yheb protein is a chitinase.